Papillary cystadenoma lymphomatosum : Case report and review of literature - Patil Karthikeya; Mahima V; Kalia Shalini (Wolters Kluwer Medknow Publications, 2005)
Papillary Cystadenoma Lymphomatosum or Warthin′s tumour is a unique neoplasm arising almost exclusively in the parotid salivary gland and is composed of oncocytic epithelium with a prominent lymphoid infiltrate. The tumor is usually asymptomatic and may be associated with varying degrees of pain not necessarily an indication of malignant transformation in the tumour. The tumour is managed easily by surgical excision. This article presents a typical case arising in the right parotid gland of a 73-year-old male with review of literature of this rare tumour.